Rethinking potentials of Co-management for sustainable common pool resources (CPR) and tourism: The case of a Mediterranean island - Alipour, Habib; Arefipour, Tahereh (Elsevier Sci Ltd, 2020)
This research explores the potentials of co-management and the state of its implementation in, which is an economy in transition and highly dependent on tourism. The study will focus on multi-level governance structure/behavior in the public sector and quasi-governmental institutions, private sector, and the role of NGOs in relation to local-level commons. Tourism is an energy intensive industry with a high carbon footprint, which immensely affects the common pool resources (CPR) and ecosystems. With such combative relation between tourism and CPR, co-management offers a solid platform for institutions and resource users to share power and collaborate to reconcile the strife between tourism and ecosystems. This study conducted an in-depth interview to obtain qualitative data. MAXQDA12 software was utilized for the data analysis. The results showed that despite an awareness of the environmental challenges and perils of mass tourism, potentials of co-management has not been realized through a multi-level governance approach to tackle the challenges. The implications and limitations are also elaborated.
Keywords: Co-management; Institutions; Power sharing; Common pool resources; Sustainable tourism; North Cyprus